Investment Dynamics in the Economies of Selected ASEAN Countries - Yaqinah, Nuriyatul Inayatil; Wilantari, Regina Niken; Yuliati, Lilis (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research is original in its dynamic panel analysis of investment efficiency determinants in ASEAN+8 economies during 2019-2023, revealing persistent efficiency patterns and nonlinear governance effects. Research Objectives: This study investigates the impact of foreign direct investment, governance quality, trade openness, and capital intensity on investment efficiency (ICOR) in ASEAN economies. Research Methods: This study employs System GMM estimation on panel data from 8 ASEAN countries. Key variables include ICOR, FDI inflows, the Corruption Perception Index, trade openness (% of GDP, and capital per worker. Empirical Results: The analysis reveals strong persistence in investment efficiency over time. While foreign direct investment has only a limited short-term effect, trade openness is a critical long-run driver of efficiency. The relationship with governance quality is complex and nonlinear. Furthermore, capital per worker was not a significant determinant of investment efficiency in the region. Implications: These results suggest ASEAN policymakers should combine FDI quality targeting with institutional reforms and maintain long-term trade liberalization commitments to enhance investment efficiency. JEL Classification: F21, O16, O53, C23 How to Cite:Yaqinah, N. I., Wilantari, R. N., & Yuliati, L. (2025). Investment Dynamics in the Economies of Selected ASEAN Countries. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 279-290. https://doi.org/10.15408/sjie.v14i2.45231.